Natural Convection in Trapezoidal Enclosure Heated Partially from Below - Mustafa, Ahmed W.; Ghani, Ihsan Ali (Al-Khwarizmi Engineering Journal, 2012)
Natural convection in a trapezoidal enclosure with partial heating from below and symmetrical cooling from the sides has been investigated numerically. The heating is simulated by a centrally located heat source on the bottom wall, and four different values of the dimensionless heat source length, 1/5, 2/5, 3/5, 4/5 are considered. The laminar flow field is analyzed numerically by solving the steady, two-dimensional incompressible Navier-Stokes and energy equations. The Cartesian velocity components and pressure on a collocated (non-staggered) grid are used as dependent variables in the momentum equations discretized by finite volume method; body fitted coordinates are used to represent the trapezoidal enclosure, and grid generation technique based on elliptic partial differential equations is employed. SIMPLE algorithm is used to adjust the velocity field to satisfy the conservation of mass. The range of Rayleigh number is (103≤ Ra ≤105) and Prandtl number is 0.7. The results show that the average Nusselt number increases with the increases of the source length.